Answer:
366127232
Step-by-step explanation:
i just divided the number and exponent and assumed x equals to 1 cause every variable is =to 1 unless it tells you what it equals to.
In(xy) = e^(x+y)
(xy)'/xy = (x+y)' e^(x+y)
(x'y + xy')/xy = (1+y') e^(x+y)
(y + xy')/xy = (1+y')e^(x+y) and simplify
Hope this helps
So a triangle is always 180°.
If one angle is 90° then we can subtract that from the 180° to find out how much the other two will be.
180°-90°=90°
So the other two angles added together will have to equal 90°.
Answer:
33
Step-by-step explanation:
9 x 3 = 27 + 6 = 33